The big book of HR - Mitchell, Barbara; Gamlem, Cornelia (Ascent Audio, 2022)
The ultimate guide to human resources challenges, issues, emerging trends, and best practices by two of the most seasoned and respected HR professionals. Every leader will agree that managing people is challenging and growing more complex. Since The Big Book of HR was first published, dramatic changes have taken place in the workplace and the workforce. This tenth anniversary edition incorporates discussions and reflections on these changes which are useful for any business owner, manager, or HR professional. The Big Book of HR, 10th Anniversary Edition includes up-to-date information about: flexibility and work; diversity, equity, and inclusion; respectful workplaces and harassment prevention; technology for today's digital workplaces; pay equity and its effect on transparency in compensation; benefits that meet the needs of a multigenerational workforce; and microlearning and employee development strategy. Get the most from your organization's talent-from strategic HR-related issues to the smallest tactical details. And, of course, there's information on remaining legally compliant, including state and local laws addressing societal changes.